Effect of reconstruction plate removal on dental implants in fibula flap mandibles: A biomechanical and clinical study - Jianyao Huang; Junpeng Chen; Jinpeng Jiang; Huiming Wang; Dan Yu; Huiyong Zhu (PLoS ONE, 2026)
Vascularized autologous bone transplantation combined with implant restoration is a preferred method for functional mandibular reconstruction. However, there is currently no consensus on whether internal fixation devices, such as titanium plates and screws, must be removed during the reconstruction process. This study aimed to assess the biomechanical and clinical necessity of removing these fixation devices. Eight patients who underwent mandibular reconstruction with fibula flaps and subsequent dental implantation were included. The study utilized finite element analysis to simulate and compare biomechanical stress distributions in models where fixation devices were either retained or removed. The clinical outcomes including peri-implant health, masticatory efficiency, and oral health-related quality of life were evaluated through follow-up examinations and standardized questionnaires. The biomechanical analysis indicated that the maximum stress on the grafted fibula surrounding the implants was significantly lower in the retention group (42.07 ± 12.06 MPa) compared to the removal group (44.892 ± 14.80 MPa, P = 0.017*). Furthermore, a positive correlation was identified between the simulated stress levels on the implants and the severity of gingival bleeding (coefficient: 0.82, P = 0.013*). Clinically, while there were no significant differences in marginal bone loss between the two approaches, patients who retained the internal fixation devices reported better quality of life scores regarding functional limitations and physical pain. In conclusion, retaining internal fixation devices appears to reduce mechanical stress on the peri-implant fibula graft and is associated with improved patient-reported outcomes. These findings suggest that the routine removal of reconstruction plates may not be necessary and that retention can favour peri-implant health and patient comfort.